1997
DOI: 10.1002/(sici)1097-0290(19971005)56:1<32::aid-bit4>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Substrate limitation in the baculovirus expression vector system

Abstract: The inability to infect insect cell cultures at the highest achievable cell densities has imposed major limitations to both the fundamental understanding of the Baculovirus Expression Vector System (BEVS) as well as full exploitation of its potential productive capacity for recombinant (β‐galAcNPV) products. The current literature does not characterize and identify the exact nature of the observed limitations, which therefore has become the major objective and contribution of the following study. Critical dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 15 publications
3
39
0
1
Order By: Relevance
“…The effects of baculovirus infection on the nutritional demands of insect cells were previously studied under different experimental conditions, with contradictory results. Several papers have reported that baculovirus-infected insect cells consume the main nutrients at higher rates than uninfected cells (Sugiura and Amman 1996;Radford et al 1997;Rodas et al 2005). However, other papers have shown that the consumption rates of the main nutrients either do not change (Wong et al 1994;Kamen et al 1996;Palomares et al 2004) or decrease (Rhiel and Murhammer 1995) after baculovirus infection in insect cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of baculovirus infection on the nutritional demands of insect cells were previously studied under different experimental conditions, with contradictory results. Several papers have reported that baculovirus-infected insect cells consume the main nutrients at higher rates than uninfected cells (Sugiura and Amman 1996;Radford et al 1997;Rodas et al 2005). However, other papers have shown that the consumption rates of the main nutrients either do not change (Wong et al 1994;Kamen et al 1996;Palomares et al 2004) or decrease (Rhiel and Murhammer 1995) after baculovirus infection in insect cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been well documented that there is a drop in cell specific yield when cells are infected at high cell densities, a phenomenon known as "the cell density effect" Caron et al, 1990;Chakraborty et al, 1996;Chan et al, 2002;Doverskog et al, 2000;Huynh et al, 2013;Radford et al, 1997;Taticek and Shuler, 1997;Wong et al, 1996). There has been much speculation as to the cause of the cell density effect, including nutrient limitation, toxic compound accumulation as well as cell-to-cell contact inhibition but the reasons for this effect remain unidentified (Doverskog et al, 1997;Taticek and Shuler, 1997).…”
Section: Introductionmentioning
confidence: 74%
“…The cell density effect has been reported mainly for Sf9 cells Caron et al, 1990;Doverskog et al, 2000;Jesionowski and Ataai, 1997;Radford et al, 1997;Reuveny et al, 1993;Taticek and Shuler, 1997;Wong et al, 1996;Yamaji et al, 1999). There are a few investigations conducted in other cell lines such as Anticarsia gemmatalis (saUFL-AG-286) (Micheloud et al, 2009), Trichopulsia ni (Hi5) (Chico and Jager, 2000;Ikonomou et al, 2004;Taticek and Shuler, 1997;Yang et al, 1996), and…”
Section: The Cell Density Effectmentioning
confidence: 99%
See 2 more Smart Citations